Waqf in History a Systematic Literature Review based on Web of Science - Quddus, Muhammad Fathrul (Ijtimā iyya Journal of Muslim Society Research, 2024)
Waqf in history is an interesting topic to discuss. By knowing the history related to waqf, a Muslim can develop broader perceptions of waqf. This study aims to determine the roles of waqf in the past to be studied and furthermore it is hoped that it can be a recommendation in managing waqf both in terms of managers and regulators. The method used in this study is a systematic literature review. The data used are articles on the Web of Science (WoS). WoS is the oldest, most widely used, and authoritative database of research publications and citations in the world. The topic keywords used in the search were “Waqf in History”, “Waqf Histories”, and “Waqf and Centuries”. The author selected 23 articles that had been screened with inclusion and exclusion criteria. Furthermore, the author divides the 23 articles into 4 major topics, namely: the role of waqf, accounting and waqf supervision, waqf regulations and rules, and waqf risks.